MENINGKATKAN KEMAMPUAN MENDENGAR SISWA SEKOLAH DASAR DALAM BAHASA INGGRIS DENGAN MENGGUNAKAN METODE TPR (TOTAL PHYSICAL RESPONSE) - DADY, KEREN; MARENTEK, ANDRIYANI; RANUNTU, GARRYN CH (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  The research is entitled "Meningkatkan Kemampuan Mendengar Siswa Sekolah Dasar dalam Bahasa Inggris dengan menggunakan Metode TPR (Total Physical Response)â€. This research is conducted in order to improve studentsâ€™ listening skills using the total physical response (TPR) method at the fifth grade of SD Negeri 70 Manado. The aims of this research were to find out whether there was an improvement of studentsâ€™ listening skills before and after being taught using the TPR method. In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. This research consisted of one cycle that consisted of four steps, they are: Planning, Action, Observation, and Reflection. To collect the data, the researcher did three steps, such as: Pre-test, Treatment, and Post-test. To analyze the data, the researcher used quantitative research design. The quantitative data were obtained from the fifth grade studentsâ€™ scores of the pre-test and post-test. The results showed that the total physical response can improve the students listening skills at the fifth grade of SD Negeri 70 Manado. The improvement could be seen from pre-test and post-test scores in the one cycle. In the pre-test, the main score is 60.95 and in the post-test, the main score is 90.55. The average score of post-test was higher than pre-test, with an increase of 48.56%. Based on the findings, it can be concluded that TPR is effective for teaching listening skill.Â Keywords: CAR, TPR Method, Listening, Quantitative Research Design, Elementary School